Proceedings of the JSPS-VCC seminar on integrated engineering, 13-14 October, 1992, Kyoto, Japan - JSPS-VCC Seminar on Integrated Engineering (4th : 1992 : Kyoto, Japan); Japan Society for the Promotion of Science (Kyoto, Japan : JSPS, 1992)
08